Earnings management, related party transactions and corporate performance: The moderating role of internal control - Grzegorz Zimon; Andrea Appolloni; Hossein Tarighi; Seyedmohammadali Shahmohammadi; Ebrahim Daneshpou (Risks, 2021)
The primary purpose of this study is to investigate the impacts of earnings management (EM) and related party transactions (RPTs) on corporate financial performance in an emerging market, Iran. This paper also aims to examine the moderating role of internal control weakness (ICW) in the relationship between them. The study sample includes 108 Iranian manufacturing companies listed on the Tehran Stock Exchange (TSE) between 2013 and 2018, and panel data with random effects are used to test the hypotheses. When an accounting-based measure called ROA is defined as a proxy for corporate performance, the results show that there is a negative association between real earnings management (REM) and corporate financial situation, while accrual-based earnings management (AEM) and firm value are correlated positively. However, when Tobin's Q index is defined as a proxy for corporate performance, we do not find any significant association between them. Consistent with the tunneling hypothesis or agency theory, our findings confirm RPTs damage corporate value (ROA and Tobin's Q) because managers probably consider it a mechanism to exploit enterprise resources owing to existing conflictual interests. Moreover, purchase-related party transactions lead to lower ROA, whereas sale-related party transactions and Tobin's Q are correlated negatively. Moreover, weak internal control has a positive moderating influence on the linkage between AEM and Tobin's Q index. Finally, we provide robust evidence that there is a positive association between sale growth and institutional owners with ROA and Tobin's Q, although financial leverage and mergers and acquisitions (M&A) have a destructive effect on corporate value.
Keywords: 330; corporate performance; earnings management; internal control weakness; related party transactions; TSE